2020
DOI: 10.1093/trstmh/traa150
|View full text |Cite
|
Sign up to set email alerts
|

Excess mortality among people with podoconiosis: secondary analysis of two Ethiopian cohorts

Abstract: Background While morbidity attributable to podoconiosis is relatively well studied, its pattern of mortality has not been established. Methods We compared the age-standardised mortality ratios (SMRs) of two datasets from northern Ethiopia: podoconiosis patients enrolled in a 1-y trial and a Health and Demographic Surveillance System cohort. Results The annual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…In addition, there was disparity in the burden of podoconiosis by gender where prevalence was higher among women (3.7%) than men (2.4%) [ 51 ]. Leg lymphedema has a significant negative socio-economic impact on people affected by podoconiosis and LF and their caregivers in co-endemic districts of Ethiopia [ 56 ] and also increases mortality [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there was disparity in the burden of podoconiosis by gender where prevalence was higher among women (3.7%) than men (2.4%) [ 51 ]. Leg lymphedema has a significant negative socio-economic impact on people affected by podoconiosis and LF and their caregivers in co-endemic districts of Ethiopia [ 56 ] and also increases mortality [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Both podoconiosis and LF are among the prioritized NTDs in Ethiopia (9). Thirteen relevant articles were identi ed (9,34,54,55,36,(47)(48)(49)(50)(51)(52)(53), that report the burden of podoconiosis or LF in Ethiopia (34,51,52). The burden of podoconiosis ranged from 0.1-8.1%, and cases of podoconiosis are widespread in Africa, where Ethiopia registered the second highest prevalence rate (7.5%), next to Cameroon (8.1%) (9,36,37,47,49).…”
Section: Podoconiosis and Lymphatic Lariasis (Lf)mentioning
confidence: 99%
“…In addition, there was disparity in the burden of podoconiosis by gender where prevalence was higher among women (3.7%) than men (2.4%) (50). Leg lymphoedema has a signi cant negative socio-economic impact on people affected by podoconiosis and LF and their caregivers in coendemic districts of Ethiopia (55), and also increases mortality (54).…”
Section: Podoconiosis and Lymphatic Lariasis (Lf)mentioning
confidence: 99%
“…It is one of the most disabling tropical diseases and reduces productivity, causes stigma from the community and healthcare professionals, and affected people report low quality of life. Although it was thought of as disabling rather than a direct cause of excess mortality, a recent study in Ethiopia demonstrated that people with podoconiosis experience greater mortality than those without podoconiosis in similar community settings (10). The treatment interventions recommended by WHO are commonly known as morbidity management and disability prevention (MMDP) or disease management, disability and inclusion (DMDI).…”
Section: Introductionmentioning
confidence: 99%